114k views
20 votes
Consider the function f (x) = x (x+3)(x – 4).
What are the zeros of the function?

User Nick Roth
by
4.8k points

1 Answer

6 votes

Answer:

The solutions are:


x=0,\:x=-3,\:x=4

Explanation:

Given the function


f(x) = x(x+3)(x - 4)

In order to determine the zeros of the function, we substitute f(x) = 0


0\:=\:x\left(x+3\right)\left(x\:-\:4\right)

switch sides


x\left(x+3\right)\left(x-4\right)=0

Using the zero factor principle

if ab=0, then a=0 or b=0 (or both a=0 and b=0)


x=0\quad \mathrm{or}\quad \:x+3=0\quad \mathrm{or}\quad \:x-4=0

Thus,

x = 0

and solving x + 3 = 0

x + 3 = 0

subtracting 3 from both sides

x + 3 - 3 = 0 - 3

x = -3

and solving x - 4 = 0

x - 4 = 0

x - 4 + 4 = 0 + 4

x = 4

Therefore, the solutions are:


x=0,\:x=-3,\:x=4

User Choppy
by
4.4k points